Isolation and Characterization of a Novel Jumbo Phage HPP-Temi Infecting Pseudomonas aeruginosa Pa9 and Increasing Host Sensitivity to Ciprofloxacin - Olufunke Olufunmilola Olorundare; Nikita Zrelovs; Dennis Kabantiyok; Karina Svanberga; Juris Jansons; Andris Kazaks; Godwin Ojonugwa Agada; Chibuzor Gerald Agu; Oluwatoyin Ruth Morenikeji; Ogundeji Alice Oluwapelumi; Thomas Dung; Shedrach Benjamin Pewan (MDPI AG, 2024)
Pseudomonas aeruginosa is a bacteria responsible for many hospital-acquired infections. Phages are promising alternatives for treating P. aeruginosa infections, which are often intrinsically resistant. The combination of phage and antibiotics in clearing bacterial infection holds promise due to increasing reports of enhanced effectiveness when both are used together. The aim of the study is to isolate and characterize a novel P. aeruginosa phage and determine its effectiveness in in vitro combination with antibiotics in controlling P. aeruginosa. In this study, a novel jumbo myophage HPP-Temi infecting P. aeruginosa Pa9 (PP334386) was isolated from household sewage. Electron micrographs of the phage were obtained to determine the morphological features of HPP-Temi virions. Complete genome analysis and a combination of Pseudomonas phage HPP-Temi with antibiotics were examined. The phage HPP-Temi was able to productively infect P. aeruginosa ATCC 9027 but was unable to infect a closely related genus. The phage was stable at 4-37 °C, 0.5% NaCl, and pH 8 for at least one hour. The HPP-Temi genome is a 302,719-bp-long dsDNA molecule with a GC content of 46.46%. The genome was predicted to have 436 ORFs and 7 tRNA genes. No virulence factor-related genes, antimicrobial resistance, or temperate lifestyle-associated genes were found in the phage HPP-Temi genome. Phage HPP-Temi is most closely related to the known or tentative representatives of the Pawinskivirus genus and can be proposed as a representative for the creation of a novel phage species in that genus. The phage and antibiotics (Ciprofloxacin) combination at varying phage titers (103, 106, 109) were used against P. aeruginosa Pa9 (PP334386) at 3.0 × 108 CFU/mL, which was carried out in triplicate. The result showed that combining antibiotics with phage significantly reduced the bacteria count at 103 and 106 titers, while no growth was observed at 109 PFU/mL. This suggests that the effect of phage HPP-Temi in combination with antibiotics is a potential and promising agent for the control of P. aeruginosa infections.